Teaching medical students basic neurotransmitter pharmacology using primary research resources. - Halliday, A; Devonshire, I; Greenfield, S; Dommett, E (American Physiological Society, 2010)
Teaching pharmacology to medical students has long been seen as a challenge, and one to which a number of innovative approaches have been taken. In this article, we describe and evaluate the use of primary research articles in teaching second-year medical students both in terms of the information learned and the use of the papers themselves. We designed a seminar where small groups of students worked on different neurotransmitters before contributing information to a plenary session. Student feedback suggested that when the information was largely novel, students learned considerably more. Crucially, this improvement in knowledge was seen even when they had not directly studied a particular transmitter in their work groups, suggesting a shared learning experience. Moreover, the majority of students reported that using primary research papers was easy and useful, with over half stating that they would use them in future study.